"Europe" in Greece: Lay constructions of Europe in the context of Greek immigration debates. (6th February 2017) - Andreouli, Eleni; Figgou, Lia; Kadianaki, Irini; Sapountzis, Antonis; Xenitidou, Maria
Abstract: In this paper, we analyse discourses about Europe in Greek debates about immigration and citizenship and highlight the complexities of "Europeanness" as a symbolic resource for argumentation in these debates. Our data consist of lay discourses from 2 rounds of online public deliberation (2009–2010 and 2015) about a controversial new citizenship law in Greece. Our analysis shows that Europe is an ambivalent category. On the one hand, Europe symbolises progress, but, on the other hand, it is also constructed in terms of decline and "contamination" by multiculturalism. Further, our analysis shows that the category of Europe can be mobilised in contradictory ways, in order to support arguments for and against citizenship rights for migrants. The paper concludes with a discussion of the ways in which constructions of Europe are implicated in processes of othering and inclusion in the context of current immigration debates. Copyright © 2017 John Wiley & Sons, Ltd.